Managing difference: Preliminary research to an enculturational care strategy in the triple periphery of Eastern Saxony, Lower Silesia and North-Eastern Bohemia - Vogt, Matthias Theodor (Tudásmenedzsment, 2023)
There may be areas in the world where reflection on strengthening intercultural resilience belongs to the group of amenities–nice to have, but not a must be, and a mere object of evening chit-chat among well-mannered people, after which the brave citizen goes to bed. The triple periphery of East Saxony, Lower Silesia and North-East Bohemia does NOT belong to this type of area. Here, on the contrary, the future of society and its economy, depends on successful intercultural resilience, and not least its political including its party-political preferences. For the following reflections, we choose the example of the care labour market and focus in particular on the situation in the German part of the European City of Görlitz-Zgorzelec as pars pro toto of the three-countries’-region. A small preliminary empirical study by Monique Ritter commissioned by us can be found in the same volume. The intercultural integration of care workers from overseas requires special efforts. Max Frisch (1965) wrote about the situation of Italian “guest workers” in Switzerland: They have called for labour, and human beings are coming. This sentence has a special truth when it comes to people who come from far away and hope to find a new home here. A critical question to be asked in the following is whether the city of Görlitz is at all suitable for such a project, and how the research can do justice to the complex situation in the border triangle. Can the findings from Leipzig (Decker et al., 2023) be transferred one-to-one to the situation in Görlitz? What insights does a more detailed analysis of crime and constitutional protection statistics offer for the safety of foreign trainees in Görlitz? What is the need for research on enculturation? This article concentrates on the background picture from which the concrete research on care will start.